Ambitious mindset (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Today, you'll learn about adopting an ambitious mindset and how to harness it to fuel growth in your career and personal life. To reach your career goals, you need to be willing to put in the hard work, focus, and effort. Ambitious people use these things to succeed in their work and personal lives. They have an inner drive and resilience that helps them stay motivated when working toward their goals. You, too, can use the same techniques to adopt the right mindset to achieve your ambitions. Learning Objectives Learn about adopting an ambitious mindset and how to harness it to fuel growth in your career and personal life Learn some of the skills you need when adopting an ambitious mindset, including surrounding yourself with the right people, competing with yourself, not others, keeping your ambitions to yourself and taking risks.